2021
DOI: 10.1007/s12282-021-01314-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pectoral breast reconstruction: early and long-term safety evaluation of 146 unselected cases of the early pre-pectoral era of a single-institution, including cases with previous breast irradiation and post-mastectomy radiation therapy

Abstract: We re-evaluated acute and early-late toxicity-related factors among pre-pectoral immediate tissue expander/implant (TE/I) breast reconstruction (BR) unselected, first-era, cases, including previous breast radiation treatment and post-mastectomy radiation therapy (PMRT). A retrospective analysis of 146 (117 therapeutic and 29 prophylactic) pre-pectoral reconstructions, between 2012 and 2016, considered patient-related (age, body mass index [BMI], smoke-history, comorbidity, BRCA mutation), and treatment-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Recently, this new technique is increasing in the high-volume centers owing to its more minimal approach. Indeed, a retrospective analysis of 146 patients showed that immediate prepectoral breast reconstruction was effective and safe with five locoregional recurrences after 4 years of follow-up and a low acute and early-late complication rates [ 17 ]. According to our data, 25% and 75% of patients received subpectoral and prepectoral breast reconstruction, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this new technique is increasing in the high-volume centers owing to its more minimal approach. Indeed, a retrospective analysis of 146 patients showed that immediate prepectoral breast reconstruction was effective and safe with five locoregional recurrences after 4 years of follow-up and a low acute and early-late complication rates [ 17 ]. According to our data, 25% and 75% of patients received subpectoral and prepectoral breast reconstruction, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical expertise and careful patient selection are the basis to achieve an excellent result with PP-IPBR [33,34]. During surgery, thickness and perfusion of skin flaps should be evaluated, in addition to individual risk factors [35], before choosing the type of reconstruction (PP vs. SM) [36,37].…”
Section: Discussionmentioning
confidence: 99%